Response to anti-DKK1 therapy in uterine carcinosarcoma: A case report - A. ElNaggar; N. Zhang; C.B. Scalise; C. Sirard; M.H. Kagey; D. Vaena; R. Arend (Elsevier, 2022)
Targeted therapies are being increasingly used in clinical practice and trials. However, tumor heterogeneity among sites of metastatic disease can occur creating a conundrum when utilizing biomarker directed therapies. Here we demonstrate a patient with recurrent uterine carcinosarcoma whose local recurrence and metastatic recurrence had a varied response to paclitaxel in combination with DKN-01, a monoclonal antibody against DKK1, a modulator of Wnt/β-catenin and PI3K/AKT signaling pathways. This may be explained by differences in mutational profile found between the two sites. Our findings highlight the importance of analyzing tissue from the primary tumor as well as metastatic lesions, especially if there is a discrepancy in their response to treatment.